THE LEGAL AUTHORITY OF FOREIGN OWNERSHIP OF AGRIKULTURAL LAND IN THE REPUBLIC OF SERBIA - Vukićević, Slavoljub; Stepić, Danica; Savović, Danilo (Economics of Agriculture, 2011)
Ownership and status of property, especially agricultural land in the Republic of Serbia, is a question that often worries foreign investors. Therefore, they find themselves in a dilemma whether it is possible to become owners of agricultural land and under what conditions. If they want to act strictly according to legal regulations, the purchase of the agricultural land is currently not possible. On the other hand, many foreigners have become the legal owners of the land and enjoy all ownership relations rights they are entitled to. This gap between legislation regulations and practices makes their status unsafe and uncertain. For that reason they often give up on their plan. Thus, the aim of this analysis is focused primarily on finding the causes that lead to this legal and factual situation, and then pointing out the ways and means how to overcome this situation. Overcoming the current situation would many benefits both to the Republic of Serbia, as well as to investors wishing to invest in our country.